PANDANGAN MAQASHID SYARIAH TERHADAP PENGGUNAAN APLIKASI KENCAN ONLINE TINDER DALAM MENENTUKAN PASANGAN HIDUP: STUDI KASUS REMAJA MUSLIM JEMBER - Ghufron Nurhakim; Triadi Wicaksono (USRAH: Jurnal Hukum Keluarga Islam, 2026)
The development of digital technology has changed the way Muslim teenagers look for life partners, including through online dating apps such as Tinder. This study aims to analyze the concept of partner selection in Islam, the practice of using the Tinder app by Muslim teenagers in Jember, and the views of Maqashid Syariah on this phenomenon. The study uses a qualitative method with a descriptive case study approach through surveys, interviews, observation, and literature studies. The results show that Islam teaches partner selection through ta'aruf by considering religion, morals, family, and environment. Muslim teenagers in Jember use Tinder to expand their social network and find partners through stages of self-introduction, sharing personal information, getting to know each other deeply, and finally determining the relationship. However, the Maqasid Syariah analysis shows that the use of Tinder contradicts the five basic principles of Sharia: Hifz ad -Din (preserving religion), Hifz an-Nafs (preserving the soul), Hifz al-Aql (preserving reason), Hifz an-Nasl (preserving offspring), and Hifz al-Mal (preserving wealth). The study concludes that Muslim teenagers in Jember should avoid this application and choose methods that are in line with Islamic values in finding a life partner.